Corporate culture as an integral part of effective functioning of the organisation - Martyniuk, Inna (My University, 2014)
Corporate culture in enterprise management system should be seen as a strategic tool that makes it possible to target all of its departments and all employees at common objectives, enhance staff initiative, ensure loyalty to the common cause, facilitate communication. The higher is the level of corporate culture the higher is the prestige and competitiveness of the enterprise.
Keywords: enterprise management; staff; corporate culture; управління підприємством; персонал; корпоративна культура; корпоративная культура; управление предприятием